2010
DOI: 10.1111/j.1365-2109.2009.02424.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility of selected feed ingredients in diets for juvenile hybrid tilapia, Oreochromis niloticus×Oreochromis aureus

Abstract: The apparent digestibility coe⁄cients (ADCs) of dry matter, crude protein, crude lipid, ash, phosphorus, gross energy and amino acids of 10 selected ingredients for juvenile hybrid tilapia (7.05 AE 0.09 g) were determined using 0.5% Cr 2 O 3 as an inert indicator. The feed ingredients tested in this study were corn gluten meal (CGM), corn byproduct, corn germ meal (CG), soybean meal (SBM), fermented soybean meal (FSM), soy protein concentrate (SPC), soy protein isolate, malt sprouts (MS), ¢sh meal (FM) and ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 24 publications
3
34
4
Order By: Relevance
“…Compared to our findings, Pezzato et al () reported lower ADCDM (54.5%), ADCGE (43.7%), and ADCCP (86.8%) in corn germ meal fed to Nile tilapia; in similar studies, Dong et al () recorded higher ADCDM (64.4%) and ADCGE (71.5%) and lower ADCCP (74.6%). Pezzato et al () reported lower ADCDM (48.8%), higher ADCGE (66.8%), and similar ADCCP (89.9%) for corn gluten fed to Nile tilapia, while Dong et al () observed higher ADCDM (59.9%), ADCGE (74.1%), and ADCCP (95.1%).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Compared to our findings, Pezzato et al () reported lower ADCDM (54.5%), ADCGE (43.7%), and ADCCP (86.8%) in corn germ meal fed to Nile tilapia; in similar studies, Dong et al () recorded higher ADCDM (64.4%) and ADCGE (71.5%) and lower ADCCP (74.6%). Pezzato et al () reported lower ADCDM (48.8%), higher ADCGE (66.8%), and similar ADCCP (89.9%) for corn gluten fed to Nile tilapia, while Dong et al () observed higher ADCDM (59.9%), ADCGE (74.1%), and ADCCP (95.1%).…”
Section: Discussioncontrasting
confidence: 73%
“…In studies of Nile tilapia, the ADCDM of corn gluten meal ranged from 74.9% (Gonçalves et al ) to 93.2%, as described by Köprücü and Özdemir (); ADCGE varied from 71.2% (Pezzato et al ) to 93.5% (Meurer et al ); and ADCCP ranged from 89.0% (Köprücü and Özdemir ) to 97.6% (Meurer et al ). Dong et al () recorded lower ADCDM (77.4%) and ADCGE (86.2%) but similar ADCCP (95.4%).…”
Section: Discussionmentioning
confidence: 89%
“…The protein quality of earthworm meal was reported to be comparable to that of fishmeal with high levels of essential amino acids for fish (Tacon et al, 1983;Tacon and Metian, 2009;Dong et al, 2010;Tuan, 2010;NRC, 2011). As in full feeds, earthworm meal was suitable as a partial replacement for fishmeal with similar or beneficial effects on fish growth (described above).…”
Section: Earthworms As a Feed Resourcementioning
confidence: 99%
“…In the literature, earthworms are generally described as resources with high protein content and protein quality but these parameters have been shown to differ according to earthworm species and, to a lesser extent, the feed substrate (Tacon et al, 1983;Stafford and Tacon, 1984;Sun et al, 1997;Changguo et al, 2006;Sogbesan et al, 2007;Dong et al, 2010;Tuan, 2010). There are several reports that demonstrate the suitability of various earthworm species as components of aqua feeds while others suggest that single earthworm species can have negative effects on the growth and health of fish.…”
Section: Earthworms As a Feed Resourcementioning
confidence: 99%
“…Protein apparent digestibility coefficient (ADC) of SPC to Nile tilapia was high and similar to that reported to hybrid tilapia (Oreochromis niloticus x Oreochromis aureus), which was 98.2% (DONG et al, 2010 However, we also registered that methionine and threonine supplementation of 100% SPC diet promoted an 11% increase in tilapia weight gain and showed significant effect on protein ADC. Therefore, despite being a good alternative source for replacing animal protein, SPC supplementation with the limiting amino acids is mandatory.…”
Section: Discussionmentioning
confidence: 73%